Polygenic impact of morningness on the overnight dynamics of sleep spindle amplitude. (17th January 2020) - Pesonen, Anu‐Katriina; Merikanto, Ilona; Halonen, Risto; Ujma, Peter; Makkonen, Tommi; Räikkönen, Katri; Lahti, Jari; Kuula, Liisa
Abstract: Sleep spindles are thalamocortical oscillations that contribute to sleep maintenance and sleep‐related brain plasticity. The current study is an explorative study of the circadian dynamics of sleep spindles in relation to a polygenic score (PGS) for circadian preference towards morningness. The participants represent the 17‐year follow‐up of a birth cohort having both genome‐wide data and an ambulatory sleep electroencephalography measurement available ( N = 154, Mean age = 16.9, SD = 0.1 years, 57% girls). Based on a recent genome‐wide association study, we calculated a PGS for circadian preference towards morningness across the whole genome, including 354 single‐nucleotide polymorphisms. Stage 2 slow (9‐12.5 Hz, N = 186 739) and fast (12.5‐16 Hz, N = 135 504) sleep spindles were detected using an automated algorithm with individual time tags and amplitudes for each spindle. There was a significant interaction of PGS for morningness and timing of sleep spindles across the night. These growth curve models showed a curvilinear trajectory of spindle amplitudes: those with a higher PGS for morningness showed higher slow spindle amplitudes in frontal derivations, and a faster dissipation of spindle amplitude in central derivations. Overall, the findings provide new evidence on how individual sleep spindle trajectories are influenced by genetic factors associated with circadian type. The finding may lead to new hypotheses on the associations previously observed between circadian types, psychiatric problems and spindle activity. Abstract : We used growth curve modelling to explore how sleep spindle activity is organized in relation to polygenic score for morningness, taking into account both the individual sleep time and level of spindle activity. The analyses revealed that those with a stronger genetic tendency towards morningness (≥ + 1 SD) displayed higher spindle amplitudes in the low‐frequency range for the most part of the night in the frontal derivation (Figure 3a, black line ≥ + 1; grey > −1 and < + 1; dotted ≤ −1). As sleep spindles contribute to sleep maintenance and brain plasticity, the found associations may underlie both associations found between low spindle activity and mental health problems.